MEMBUDAYAKAN TEATER DI SMA NEGERI TANJUNGSARI, SUMEDANG - Banita, Baban; Gumilar, Trisna; Sarathan, Indra (Midang, 2025)
Playing theater is an activity that involves other types of art. Therefore, someone who wants to be active or involved in the world of theater needs to equip themselves with various skills, such as acting, music, dance, makeup, decoration, and others. Playing theater can be done by various age levels as long as they are able, willing, and physically and mentally healthy. For high school students, playing theater is very useful for increasing knowledge, intelligence, organizational skills, and social skills because playing theater contains processes that are in line with these uses. In order to increase appreciation and sustainable activities in the field of theater, the Community Service Team (PKM), Faculty of Cultural Sciences, Padjadjaran University held training at Tanjungsari State High School, Sumedang, specifically for the Gulamsaka Theater Group. The materials presented at the activity were the History of Indonesian Theater, Literature and Theater, Script Analysis, Theater Playing Practice (body, soul, vocal). The techniques used in this activity are divided into three forms: direct explanation, discussion, and practice. This activity was attended primarily by new members of Gulamsaka and several committee or senior members, and was attended by teachers supervising extracurricular activities. The event took place over several days, from 2:30 PM to 5:00 PM WIB. The result was the formation of a team that would perform a short play.